Effect of different cryoprotectants and sperm densities of orange mud crab, Scylla olivacea (Herbst, 1796) for long-term storage of spermatozoa - Mhd Ikhwanuddin; Teng Phei Yin; Abdul Jabbar Menon; Safiah Jasmani; Ambok Bolong Abol-Munafi (Universiti Kebangsaan Malaysia, 2015)
The objectives of this study were to determine the effect of different cryoprotectants and sperm densities for long-term storage of orange mud crab, Scylla olivacea spermatozoa. Spermatozoa were obtained by homogenizing the spermatophores using a glass homogenizer in an ice-bath followed by centrifugation at 4°C. Spermatozoa were then suspended in calcium-free saline (Ca-F saline) containing 5% of the following cryoprotectants: Glycerol, dimethyl sulfoxide (DMSO) and methanol. Sperm which vibrated and rotated were counted as live during sperm viability assessment. Samples of spermatozoa were cooled to -196°C by two-step freezing, first to -80°C and then by plunging into liquid nitrogen (LN). Spermatozoa were gradually cooled at 1°C/min. Thawing was carried out in a 30°C water bath for 2 min. This yielded live sperm after storage in LN for 30 days. The best sperm viability was obtained from a density of 108 cells per mL in DMSO. There was no significant difference (p>0.05) among cryoprotectants toward sperm viability. However, sperm viability was significantly affected (p>0.05) by cell densities. In conclusion, DMSO gave the best protection to sperm cells of S. olivacea, but the effectiveness of DMSO as a cryoprotectant is influenced by sperm density.